An Empirical Analysis on COVID-19: Lockdown Impact on Nigerian Economy - Hayatuddin Hamza Safiyo; Ahmed Ibrahim Mohammed; Muhammad Bello Jakada; Umar Musa Kallah; Bashir Usman Mika'il (Journal of Accounting Research, Organization and Economics, 2020)
Objective – Objective of this study is to analyze the lockdown effect on economic activities in Nigeria as the lockdown response measure to COVID-19 pandemic claim to pose a serious and potentially long term socio-economic threat to individuals, households, businesses as well as public sectors in Nigeria. Design/methodology – This study considered four regions in Nigeria (Northwest, North-Central, South-South and Southeast) and adopted a quantitative research approach which entails systematic evaluation of individuals’ behavior towards an unprecedented economic shock and their response to the manner in which the situation might unfolds by lifting the lockdown measure in Nigeria. This is achievable with a systematic random sample and a well-structured survey questionnaire. All these regions experienced the imposition of lockdown measure by their respective state authorities. Results – The results indicated that most socio-economic challenges including job loss, increase social vices, rise in poverty level, fall in economic activities, as well as fall in the level of GDP faced by individuals was not a resultant of the lockdown. Consequently, authority’s inefficiency was also challenged in spite of their efforts to mitigate and control the emerging economic consequences faced by households during the lockdown periods.Recommendation - The study recommends that lifting of lockdown would be the best action for the government to take for socio-economic resilience. The study also revealed that both public and individuals need to establish democratic preferences, and trust on health professionals or experts. Further to this, government should decide on effective measures needed to contain the continuous spread of the virus especially through development of research based and healthcare institutions.